Early Versus Late Tracheostomy: An Umbrella Review and Meta-Analysis - Sven Mostberger; Marija Glisic; Magda R. Gamba; Claudio Perret; Gabi Mueller (Journal of Clinical Medicine, 2026)
Background: Optimal tracheostomy timing remains controversial due to conflicting evidence across published systematic reviews. To clarify this ambiguity within specific patient populations (critically ill, traumatic brain injury, stroke, trauma, COVID-19, and spinal cord injury), an umbrella review of systematic reviews was conducted comparing early versus late tracheostomy or prolonged intubation. Additionally, potential benefits in clinical outcomes were evaluated across a mixed-etiology cohort of mechanically ventilated patients. Methods: MEDLINE, Embase, Cochrane Library, and Web of Science were searched from inception through July 2024. Systematic reviews evaluating the impact of tracheostomy timing on mechanical ventilation duration, ventilator-associated pneumonia risk, ICU/hospital length of stay, and mortality were included. Two authors independently extracted data using a standardized form. Methodological quality was assessed via AMSTAR 2 and certainty of evidence via GRADE. Random-effects meta-analyses were conducted for each outcome, stratified by study design (RCTs vs. non-RCTs), with subgroup analyses exploring patient subpopulations. Results: Evidence was synthesized from 9 systematic reviews (24 unique RCTs, 54 non-RCTs). In RCTs, moderate certainty evidence suggests that early tracheostomy reduces ventilator-associated pneumonia (OR 0.66, 95% CI 0.46 to 0.94, p = 0.02) and mechanical ventilation duration (MD −3.76 days, 95% CI −6.01 to −1.52, p < 0.001) compared to late tracheostomy or prolonged intubation. Early tracheostomy may reduce ICU length of stay (MD −6.64 days, 95% CI −9.92 to −3.35, p < 0.001, low certainty). The effect of early tracheostomy on hospital length of stay and mortality remains uncertain. Conclusions: Early tracheostomy shows potential to reduce ventilator-associated pneumonia and mechanical ventilation duration in mixed-etiology cohorts. It may also be associated with shorter ICU length of stay, while its effect on mortality and hospital stay remains uncertain. Future research should establish standardized definitions of tracheostomy timing and prioritize high-quality, etiology-specific RCTs in underrepresented cohorts (e.g., traumatic brain injury, stroke, spinal cord injury).